2016
DOI: 10.1111/imm.12638
|View full text |Cite
|
Sign up to set email alerts
|

High‐density lipoprotein reduces inflammation from cholesterol crystals by inhibiting inflammasome activation

Abstract: Interleukin-1β (IL-1β), a potent pro-inflammatory cytokine, has been implicated in many diseases, including atherosclerosis. Activation of IL-1β is controlled by a multi-protein complex, the inflammasome. The exact initiating event in atherosclerosis is unknown, but recent work has demonstrated that cholesterol crystals (CC) may promote atherosclerosis development by activation of the inflammasome. High-density lipoprotein (HDL) has consistently been shown to be anti-atherogenic and to have anti-inflammatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 52 publications
3
77
1
3
Order By: Relevance
“…The relationship between the respective functions of SAA and HDL is complex: While HDL enriched in SAA is thought to be impaired in its anti-inflammatory properties (62,63), many of the proinflammatory effects of SAA have been attributed to lipid-free, and not HDL-associated SAA (41). In our study, we report that HDL completely masks SAA- HDL is known to inhibit inflammasome activation by other stimuli including cholesterol crystals, ATP, nigericin, silica and alum (42) in THP-1 cells, a monocytic cell line that requires no priming for inflammasome activation. On the other hand, in our studies, HDL did not alter LPS/ATPinduced IL-1β secretion, even though there was a trend for HDL to decrease LPS-mediated IL-1β mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The relationship between the respective functions of SAA and HDL is complex: While HDL enriched in SAA is thought to be impaired in its anti-inflammatory properties (62,63), many of the proinflammatory effects of SAA have been attributed to lipid-free, and not HDL-associated SAA (41). In our study, we report that HDL completely masks SAA- HDL is known to inhibit inflammasome activation by other stimuli including cholesterol crystals, ATP, nigericin, silica and alum (42) in THP-1 cells, a monocytic cell line that requires no priming for inflammasome activation. On the other hand, in our studies, HDL did not alter LPS/ATPinduced IL-1β secretion, even though there was a trend for HDL to decrease LPS-mediated IL-1β mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Our group previously reported that lipid-poor SAA, but not HDL-associated SAA, stimulates granulocyte colony stimulating factor and TNFα production in macrophage cells (41). HDL suppresses inflammasome activation triggered by cholesterol crystals (42). It was therefore of interest to investigate whether HDL-associated SAA induces IL-1β secretion in J774 cells similarly to purified, lipid-poor SAA.…”
Section: Hdl Inhibits Saa-induced Il-1β Transcription and Secretionmentioning
confidence: 99%
“…High cholesterol concentrations in atherosclerotic plaque result in the formation cholesterol crystals, which have been shown to trigger inflammasome activation via a complement dependent mechanism (109). Reconstituted HDL (rHDL) binds to cholesterol crystals and inhibits crystal induced activation of complement and also prevents crystal induced production of inflammatory cytokines in whole blood (110, 111). These studies provide convincing evidence that a lack of HDL can result in excessive complement activation, and highlight the importance of HDL in suppressing complement induced inflammatory activities.…”
Section: Potential Roles For Protease Regulation By Hdlmentioning
confidence: 99%
“…Estos complejos pueden ser activados por cristales de colesterol, los cuales al ser fagocitados por los macrófagos, inducen una respuesta inflamatoria con la liberación de IL-1β e IL-18 (25,26). Recientemente se ha demostrado que las HDL tienen la capacidad de disminuir la secreción de IL-1 en repuesta al estímulo con cristales de colesterol en macrófagos derivados de monocitos y la línea celular TPH-1; esta reducción podría asociarse con la capacidad de las HDL de modular negativamente la expresión transcripcional de NLRP3 e IL-1β, así como de inducir una mayor estabilidad de la membrana lisosomal reduciendo la activación de la caspasa-1 y el daño mitocondrial (27). Por otra parte, dado el papel que tienen las HDL en el trasporte del colesterol, se han realizado diversos estudios para determinar su efecto en las lesiones ateroescleróticas.…”
Section: Papel De Las Hdl Durante Respuesta Inflamatoria Agudaunclassified